Perlindungan Hukum terhadap Anak Korban Tindak Pidana - M. Iqbal (Kanun Jurnal Ilmu Hukum, 2011)
ABSTRACT: Child abuse is often difficult to discover because it is domectic case.  Physic harrassment and victim of the crime result in children become weak and hurted physically and physicologically. As next generations, they must be protected in order to secure and protect them and their rights namely; right to life, right to grow and to participate optimally in compliance with human dignity and get protected from abuse and discrimination. The method applied is juridical normative approach. The aim of this research are to know the causes of such abuse and the law protection on them. The findings are the cause of such abuse are caused by multiple factors; internal and eksternal. The child abuse is conducted by the people that have responsibility to protect them and have power over them that they actually shoould protect them. The law enforcement for such offence in Indonesia can be said that it is still lack. Law Protection on Children as a Crime Victim